Beyond Ritual: The Slametan Tradition as a Transformative Adult Learning Space in the Osing Community - Muhammad Irfan Hilmi; Arief Hendrawijaya; Achmad Hufad; Nani Sintiawati; Sucianingsih Sucianingsih (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2026)
Whereas indigenous rituals are commonly considered instruments of cultural preservation, the study asserts that they are a complex, highly effective, andragogical system that helps adults learn to transform. With the Slametan culture of the Osing Kemiren community in Indonesia as one of its focal points, this study challenges the dominance of Western, individualist formulations of education by developing the theme of communal practices that promote adult development. A qualitative ethnographic design was employed to collect data through participatory observation and in-depth interviews with adult participants and community elders (Pinar). The results indicate that Slametan is a Community of Practice (CoP) in which adults advance from peripheral involvement to spiritual leadership. Importantly, the ritual in the role of transformative learning, specifically, the Ruwatan (purification) part in the study, allows adults to overcome the dilemmas of life crises (disorienting dilemmas) by critically examining themselves and engaging in spiritual dialogue. Also, the tradition facilitates ecological andragogy, whereby adults must master local ecological knowledge to make rituals effective. This paper finds that the holistic approach to adult education provided by the Osing model integrates spiritual, social, and ecological aspects that are usually divided in formal Western andragogy.